The A2Π–X2Σ+ Band System of ScO for M-type Star Spectral Analysis - Léo Lavy; Adam Pastorek; Peter F Bernath (The Astrophysical Journal)
M-type stars are the most abundant stars in our Galaxy. Their visible spectra are characterized by strong TiO and VO absorption bands with occasional ScO bands near 6000–6100 Å. This region corresponds to the A ^2 Π–X ^2 Σ ^+ band system and can be used to measure the abundance of ScO. In this work, a new Doppler-limited resolution spectrum of ScO obtained in a hollow-cathode experiment is presented. The A ^2 Π–X ^2 Σ ^+ electronic transition is analyzed with special care dedicated to fitting the ${{\rm{A}}}^{{′} 2}{\rm{Δ }}(v+2)$ ∼ A ^2 Π( v ) perturbation. Spectroscopic constants of the A ^2 Π( v ) states are reported for v ≤ 9, and a partial fit of spectroscopic constants is made for the ${{\rm{A}}}^{{′} 2}{\rm{Δ }}(v)$ states 2 ≤ v ≤ 6. The modeled interaction of the two states reproduces the experimental data remarkably well. New equilibrium constants are extracted from the fit. Band strengths are calculated with the help of a scaled transition dipole moment function, previously calculated with ab initio methods. Finally, a line list of the A ^2 Π–X ^2 Σ ^+ band system is provided, including Einstein A coefficients and oscillator strengths. Using this line list, the spectrum of ScO can be simulated for different temperature and pressure conditions in stellar atmospheres.